Application of comprehensive score of risk factors to determine the best time for surgical intervention in neonatal necrotizing enterocolitis. (20th November 2022) - Rao, Hongping; Xie, Yanmei; Zhou, Yuxiang; Liao, Zhihang
Abstract : Aim: Necrotizing enterocolitis (NEC) is a severe digestive systemic disease. Surgery is critical treatment for NEC patients. However, it is still hard to predict the optimal timing of surgery. Our study aimed to explore the indicative effect of comprehensive risk factors method in surgical intervention in NEC patients. Methods: Retrospective analysis was made on newborns with NEC, who were divided into group I (patients with NEC conservative therapeutic approach or no necrosis or perforation found in NEC operation) and group II (patients with necrosis or perforation found in NEC operation or failure of NEC conservative approach). Clinical manifestations and complications were recorded and the risk factors scores were calculated. The receiver operating characteristic curve and Youden index were calculated. Results: One hundred and six NEC patients in Huizhou Central People's hospital were analysed. Significant difference was observed in the comprehensive scores of the two groups to judge the indications of NEC surgery. Among the risk factors of NEC surgery, the incidence specificity of abdominal induration, abdominal tenderness, hypotension and pneumoperitoneum was 100% in group II. The area under the curve of the comprehensive score of risk factors was 0.981 (95% confidence interval 0.958–1.000). The best cutoff value obtained by the maximum Youden index is 3.5 (sensitivity 97.2%; specificity 52.8%). When the specificity is 100%, the best interception value is 7.5 (sensitivity 91.4%; specificity 100%). Complications such as surgical intervention, mortality, stenosis after conservative treatment, perforation or necrosis during surgery were significantly different in different comprehensive scores. Conclusions: Abdominal induration, abdominal tenderness, hypotension and pneumoperitoneum are independent predictors of NEC surgery. Comprehensive risk factors score may be a potentially useful clinical decision‐making tool for NEC surgery.